Glucosinolates in Lepidium campestre - Isoz, Michaela (2018)
Field cress (Lepidium campestre) is today not a domesticated crop for public consumption. Lepidium campestre is a relative to rapeseed (Brassica napus) and both are producing oil. Lepidium campestre contain glucosinolates which makes it unattractive for food and feed, however, it has some other properties that makes it attractive in a plant culture point of view. Field cress has a better cold tolerance than rapeseed which means that it can be grown further north. Moreover, Lepidium campestre is a perennial crop that can help minimise tillage and therefore help to minimise nitrogen leaching. Glucosinolates is a b-thioglucoside-N-hydroxysulfates that exist in the whole plant but, it is most concentrated in the seeds. Today we know about 130 glucosinolates that are categorised by both structure and the amino acids. Glucosinolates are by itself not toxic, however if the plant is damaged and glucosinolates reacts with the enzyme myrosinase then several products are produced which could be toxic, some studies have shown toxicity in mice and rats. In this study, a method based on an earlier method was modified to be able to analyse glucosinolates in Lepidium campestre in a cheaper and faster way. This was done by trial and error testing using the results from the tests and modifying the method after that. Two important steps for making the analysis successful was to use a sinigrin calibration curve and a purified sulfatase. The results from the Lepidium campestre analysis showed that one glucosinolate was the dominant one in all the samples which is most likely sinalbin. Twenty-two different Lepidium campestre seed samples from three different countries were analysed for the glucosinolate content. The result showed that the content of glucosinolates varied between 180 and 360 µmol/g in all samples except one from Sweden which had a content of almost 600 µmol/g. The mean value for the samples from Sweden was 289 µmol/g, from Germany 273 µmol/g and from USA 292 µmol/g. There was no significant different in glucosinolate content between samples from different countries.